1997
DOI: 10.1128/cdli.4.3.314-320.1997
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of mycobacterium cell wall extract (Regressin) on lymphocyte blastogenic activity and macrophage cytokine gene transcription in swine

Abstract: Mycobacterium cell wall extract (MCWE) (Regressin) contains trehalose dimycolate and muramyl dipeptide, both of which have immunomodulatory properties. The goal of this study was to evaluate the effect of MCWE on the in vitro peripheral blood lymphocyte blastogenic activities to mitogens phytohemagglutinin (PHA) and concanavalin A (ConA) in 6-to 8-week-old piglets. The effect of MCWE on alveolar macrophage tumor necrosis factor alpha (TNF-␣) and interleukin-1␤ (IL-1␤) gene transcription, as determined by a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In fact, stimulatory effects of these adjuvants on Th1 cells have also been observed 23 . Previous studies also showed effects of calf spleen extract on the immune system 13–16 and potential clinical immunotherapeutic effects of Mycobacteria , 17–21 supporting the findings from the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, stimulatory effects of these adjuvants on Th1 cells have also been observed 23 . Previous studies also showed effects of calf spleen extract on the immune system 13–16 and potential clinical immunotherapeutic effects of Mycobacteria , 17–21 supporting the findings from the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The hygiene hypothesis suggests that early‐life environmental exposure to microbes, other pathogens and their products promotes innate immune responses that suppress atopy, including both Th1‐type patterns 17 . Mycobacterium cell wall extract can stimulate lymphocyte functional activity and cytokine mRNA expression in swine, 18 and exposure to Mycobacteria or mycobacterial proteins led to subsequent reduction in different atopic manifestations 19 . Intratracheal administration of M. vaccae ameliorated airway histopathological features in a murine asthma model, 20 and effects of heat‐killed M. vaccae (SRL172) on allergen‐induced airway responses have also been demonstrated 21 …”
Section: Introductionmentioning
confidence: 99%
“…The promotion of innate immune responses and atopy suppress; which include TH1-type patterns in individuals with early-life environmental exposure to microorganisms and their products were documented ( 14 ). Stimulation of lymphocyte functional activity and cytokine mRNA expression in swine by mycobacterium cell wall extract was also shown ( 15 ). Exposure to Mycobacteria or mycobacterial proteins led to reduction in different atopic manifestations ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the products available on the market, a mycobacterium cell wall fraction immune stimulant is approved for the reduction of clinical signs and mortality associated with K99 Escherichia coli diarrhea in neonatal calves (Amplimune®, NovaVive Inc., Napanee, ON, Canada). Additionally, mycobacterium cell wall fraction immune stimulants have been shown to modulate innate immune response and stimulate lymphocyte functional activity, in vivo and in vitro , in other species within hours of administration and last only for a few days ( 22 25 ). Considering that immune stimulation can induce early activation of the non-specific innate immune system of newborn dairy calves and provide the first line of defense against microbial pathogens ( 26 , 27 ), this study was designed to evaluate the effects of this commercially available IS on health and performance of pre-weaned Jersey and Jersey-cross calves following transportation.…”
Section: Introductionmentioning
confidence: 99%